2021
DOI: 10.1111/ene.14831
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID‐19 pandemic and a national lockdown on hospitalizations for stroke and related 30‐day mortality in France: A nationwide observational study

Abstract: The COVID-19 pandemic greatly overwhelmed healthcare facilities around the world, including France. French hospitals were reorganized at a local level to optimize the management of patients infected by SARS-CoV-2 [1]. France was one of the main European countries where the SARS-CoV-2 virus initially spread, leading to a marked excess mortality in March and April 2020 [1,2]. A national lockdown was implemented from March 17 to May 11, 2020 (weeks 12 to 19), targeting a population of 66 million inhabitants. Lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 35 publications
2
25
0
1
Order By: Relevance
“…A significantly lower number of hospital admissions of patients with myocardial infarction was reported during the lockdown compared to before the pandemic [4]. The same trend was observed for stroke [5], mental health care [6], oral cancer diagnosis [7], oncologic management [8] and diabetes [9].…”
Section: Introductionmentioning
confidence: 58%
“…A significantly lower number of hospital admissions of patients with myocardial infarction was reported during the lockdown compared to before the pandemic [4]. The same trend was observed for stroke [5], mental health care [6], oral cancer diagnosis [7], oncologic management [8] and diabetes [9].…”
Section: Introductionmentioning
confidence: 58%
“…Gabet et al [13] reported that mortality increased during the lockdown period in France and subsequently returned to the baseline. In our study, the mortality rate peaked in the early post-period and returned to the expected rate.…”
Section: Ischemic Strokementioning
confidence: 99%
“…Delayed basic and advanced life support significantly impact the outcome of cardiac arrest [9]. The worsening outcomes of time-sensitive diseases were reported during the COVID-19 pandemic [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations